Mapping climate vulnerability and poverty in Africa - Thornton, Philip K.; Jones, Peter G.; Owiyo, T.; Kruska, Russell L.; Herrero, Mario; Kristjanson, Patricia M.; Notenbaert, An Maria Omer; Bekele, N.; Omolo, Abisalom (International Livestock Research Institute, 2006)
The world’s climate is continuing to change at rates that are projected to be unprecedented in recent human history. Some models are now indicating that the temperature increases to 2100 may be larger than previously estimated in 2001. The impacts of climate change are likely to be considerable in tropical regions. Developing countries are generally considered more vulnerable to the effects of climate change than more developed countries, largely attributed to a low capacity to adapt in the developing world. Of the developing countries, many in Africa are seen as being the most vulnerable to climate variability and change. High levels of vulnerability and low adaptive capacity in the developing world have been linked to factors such as a high reliance on natural resources, limited ability to adapt financially and institutionally, low per capita GDP and high poverty, and a lack of safety nets. The challenges for development are considerable, not least because the impacts are complex and highly uncertain. The overall aims of DFID’s new research programme on climate change and development in sub-Saharan Africa are to improve the ability of poor people to be more resilient to current climate variability as well as to the risks associated with longer-term climate change. The programme is designed to address the knowledge implications of interacting and multiple stresses, such as HIV/AIDS and climate change, on the vulnerability of the poor, and it will concentrate on approaches that work where government structures are weak. To help identify where to locate specific research activities and where to put in place uptake pathways for research outputs, information is required that relates projected climate change with vulnerability data. ILRI undertook some exploratory vulnerability mapping for the continent in late 2005 and early 2006, building on some livestock poverty mapping work carried out in 2002. The work described here is a small piece of a larger activity that involved the commissioning of several studies on climate change and the identification of the critical researchable issues related to development. A project inception meeting was held with research collaborators, to discuss analytical approaches and assess data availability. Over the succeeding few months, data were assembled and analysis undertaken. This involved the downscaling of outputs from several coupled Atmosphere-Ocean General Circulation Models (GCMs) for four different scenarios of the future, and possible changes in lengths of the growing period were estimated for Africa to 2050 for several different combinations of GCM and scenario (we used the SRES scenarios of the IPCC). Results are presented on the basis of agricultural system types by country, using a systems classification as a proxy for the livelihood options available to natural resource users. From this, we identified areas that appear to be particularly prone to climate change impacts. These include arid-semiarid rangeland and the drier mixed systems across broad swathes of the continent, particularly in southern Africa and the Sahel, and coastal systems in eastern Africa. The next stage was to consider the biophysical and social vulnerability of these and other areas. To characterise sub-Saharan Africa in terms of vulnerability, on the same country-by-system basis as was done for the climate change impacts, a set of proxy indicators developed at the workshop was pragmatically assessed in relation to data sources, while being guided by the experiences of others in the area. A final set of fourteen indicators was used; three are associated with natural capital, one with physical capital, two with social capital, six with human capital, and two with financial capital. We carried out statistical analysis and reduced this set of fourteen proxy indicators to four components, which were then used to construct an “overall” indicator of vulnerability, and systemsby- countries were then classified in quartiles. These results were then qualitatively combined with the climate change hotspot analysis. The results should be treated as indicative only, and we would caution strongly against their over-interpretation, particularly because the uncertainty associated with them is not yet known. Results do indicate, however, that many vulnerable regions are likely to be adversely affected in sub-Saharan Africa. These include the mixed arid-semiarid systems in the Sahel, arid-semiarid rangeland systems in parts of eastern Africa, the systems in the Great Lakes 4 region of eastern Africa, the coastal regions of eastern Africa, and many of the drier zones of southern Africa. There are several limitations to the analysis and to the availability of data for such work. For the future, considerable emphasis needs to be placed on collaborative efforts to collect and greatly improve the store of baseline information, on understanding very well the needs of potential users, on developing more flexible and generic frameworks for assessing vulnerability, taking advantage of the experiences of others in vulnerability assessment work in developing-country contexts through southsouth collaboration, and on incorporating scenario analysis into the impact assessment framework. The project also involved a study of the potential uses of information concerning climate variability and climate change for effective decision-making. A small survey of potential users was carried out. Findings of the survey confirm the results of other scoping studies: there are broad needs across many different sectors in terms of capacity building and opportunities for research in the future, including vulnerability mapping at different levels. The report concludes with a discussion of the feasibility of expanding the methods and tools used here to develop a tool box that could be used for cross-sectoral ex-ante assessment of interventions related to climate change and coping mechanisms. There are several challenges that have to be addressed, but there are good prospects for developing a useful framework. The work has highlighted two other key points. First, even allowing for the technical problems and uncertainties associated with the analysis, it is clear that macro-level analyses, while useful, can hide enormous variability concerning what may be complex responses to climate change. There is considerable heterogeneity in households’ access to resources, poverty levels, and ability to cope. Vulnerability and impact assessment work can certainly be usefully guided by macro-level analyses, but ultimately this work has to be done at regional and national levels. Second, these results have underlined that local responses to climate change through time are not necessarily linear. In terms of adaptation strategies, far more work is needed on the dynamics of change through time and on the dynamics of household responses. If adaptation itself has to be seen as an essentially dynamic, continuous and non-linear process, this has considerable implications for the tools and methods needed to guide it, and for the indicators and threshold analyses that will be needed. The sciences of climate modelling and vulnerability assessment are developing rapidly, and over time some of the key technical issues that remain are likely to be resolved. At the same time, there are several other issues that have to be addressed. One is the necessity of communities starting to take centre stage in conducting vulnerability analysis and implementation to enhance their long-term capacities for adaptation. Another is the organisational changes that are needed to face the threat that climate change poses to development: climate change is inevitable, and it will add burdens to those who are already poor and vulnerable. A third issue is that Africa appears to have some of the greatest burdens of climate change impacts, certainly from the human health and agricultural perspectives; it is a region with generally limited ability to cope and adapt; and it has some of the lowest per capita emissions of the greenhouse gases that contribute to global warming. The likely impacts of climate change thus present a global ethical challenge as well as a development and scientific challenge, and this challenge has to be addressed by all of us.